EFFECTIVENESS AROMA THERAPY GOTU KOLA (CENTELLA ASIATICA) AGAINST INSOMNIA DISORDER - Mingle A Pistanty (Literasi Nusantara, 2022)
Centella asiatica) aroma therapy against insomnia disorders. This research is an experimental study with a quasi-experimental design pre and post test without control. The research method used is an experimental method by testing the aromatherapy effect of gotu kola leaf ethanol extract on mice as test animals, with drugs. The result is the romantherapy effect of gotu kola (Centella asiatica) on insomnia disorders, this is because the sedative effect of gotu kola involves: GABA receptors in the central nervous system. The content of gotu kola which consists of brahmoside and brahminoside works to upgrade GABA through a cholinergic mechanism. The conclusion of the study showed that there was a significant difference between the level of insomnia before giving aromatherapy and after giving aromatherapy to research subjects.